Translation, Cultural Adaptation and Contributions to the Validation of the Nijmegen Cochlear Implant Questionnaire (NCIQ) for European Portuguese - Roque Reis, Luis; Castelhano, Luís; Gani, Kaamil; Correia, Filipe; Nunes, Gonçalo; Santos, Ricardo; O'Neill, Assunção; Escada, Pedro (Acta Médica Portuguesa, 2022)
Introduction: The Nijmegen Cochlear Implant Questionnaire (NCIQ) scale uses a simple and easily administered questionnaire to evaluate the adaptation of individuals to their cochlear implants. The aim of this study was to validate the NCIQ for European Portuguese, through its translation and cultural adaptation. It also presents the evaluation of reproducibility and the description of the results of this questionnaire in patients using IC. Material and Methods: Fifty postlingually deaf adult multichannel cochlear implant users (uni- or bilateral) participated in the study. Participants used the cochlear implant for at least 12 months and were patients of the Department of Otolaryngology at the Egas Moniz Hospital in Lisbon. Permission, as well the guidelines for translation, were obtained from the authors of the scale. Translation and cultural adaptation were carried out, in addition to the evaluation of reproducibility and internal consistency. Results: The participants were 44.0% male and 56.0% female, aged between 20 and 79 years (55.50 ± 15.69). The results of the study showed an overall level of satisfaction of 65.07 among cochlear implants users. The level of satisfaction of the subdomains was 64.40 in basic sound perception, 71.35 in advanced sound perception, 57.91 in speech production, 59.05 in self-esteem, 69.75 in activity and 68.50 in social functioning. Internal consistency (Cronbach α score = 0.96) and test-retest reliability coefficients proved to be strong. Furthermore, the questionnaire’s overall and subdomains average scores did not differ significantly from the results obtained with the original scale. Conclusion: This adaptation of the NCIQ questionnaire for European Portuguese should be considered a good tool to evaluate the level of satisfaction of cochlear implant users and, so far, it is the only scale in this field validated for application in the Portuguese population.